Study on the Microstructure, Mechanical Properties, and Erosive Wear Behavior of HVOF Sprayed Al2O3-15 wt.%TiO2 Coating with NiAl Interlayer on Al-Si Cast Alloy - Marzanna Ksiazek (Materials, 2020)
Alumina oxide coatings are widely used in many industrial applications to improve corrosion protection, wear and erosion resistances, and thermal insulation of metallic surfaces. The paper presents study of the microstructure, mechanical, and wear properties of HVOF (high velocity oxy-fuel process) sprayed of Al2O3-15 wt.% TiO2 coating with the NiAl interlayer on the surface of Al-Si alloy castings. The microstructure of Al2O3-15 wt.% TiO2/NiAl coating was characterized by light microscopy, X-ray diffraction (XRD), scanning electron microscope (SEM), and energy dispersive X-ray spectroscopy (EDS). The analysis of the microstructure showed the formation of coating with low porosity, compact structure, good adhesion to the substrate with typical lamellar structure composed of a solid phase consisting of compounds included in the coating material and their phase variations. For analysis of the adhesion of coatings to the substrate, the scratch test was applied. An assessment of the erosive wear resistance of coatings was also carried out, confirming the significant impact of the interlayer as well as the microstructure and phase composition of the oxide coating on the wear resistance of the tested coating system. Moreover, the results were discussed in relation to the bending strength test, including cracks and delamination in the system of the Al2O3-15 wt.% TiO2/NiAl/Al-Si alloy as microhardness and erosion resistance of the coating. It was found that the introduction of the NiAl metallic interlayer significantly increased resistance to cracking and wear behavior in the studied system.